The impact of demographic and clinical characteristics on diabetic painful neuropathy - Assunção, António; Campos, Dina; Marques, Rui; Cunha, Inês; Santos, Patrícia; Martins, Adriana; Gonçalves, Ana Sofia; Rebelo, Ana; Lima, Carolina; Matos, César; Prata, Ana Cristina; Teixeira, José Tiago; et al. ("N Gh Lupu" Foundation of Internal Medicine and Romanian Academy, 2020)
Introduction: Diabetic neuropathy (DN) is one of the most devastating complications of diabetes mellitus; however, in contrast to other countries, there are no scientific studies in Portugal evaluating the impact of demographic and clinical characteristics of this pathological entity. The aim of this study was to evaluate the impact of gender, metabolic control, age of diabetic patients, as well as time of disease progression, the appearance of complaints related to neuropathic pain. Material and methods: A multicentre study with a non-probabilistic, convenience sample of 359 patients was performed employing the quantitative method, using the Statistical Package for Social Science 24 software. The p-value of p < 0.05 was defined to consider a result statistically significant. The Spearman correlation coefficient (r) was determined to determine the relationship between categorical variables. Results: There was no statistically significant difference in the prevalence of DN between genders (p = 0.633 and r = 0.025). There was a statistically significant relationship between the value of HbA1c and DN, with p = 0.010 and r = 0.136. There is a relationship between age and complaints of neuropathic pain, with p = 0.034 and r = 0.112. The variable, time of disease progression, is also correlated with the appearance of complaints of neuropathic pain with p = 0.020 and r = 0.112. Conclusion: The prevalence of neuropathic pain in subjects with diabetes is not negligible and is associated with modifiable risk factors that can be identified, possibly modified and prevented. The correct approach for these patients, which involves screening and early treatment, is decisive improving functionality and quality of life.
Keywords: Age of Onset; Aged; Diabetic Neuropathies; Disease Progression; Female; Glycated Hemoglobin A; Humans; Male; Middle Aged; Quality of Life; Risk Factors; Sex Factors; Time Factors